The folding mechanism of a dimeric β-barrel domain - de Prat Gay, Gonzalo (2005)
The dimeric β-barrel domain is an unusual topology, shared only by two viral origin binding proteins, where secondary, tertiary and quaternary structure are coupled, and where the dimerization interface is composed of two four-stranded half-β-barrels. The folding of the DNA binding domain of the E2 transcriptional regulator from human papillomavirus, strain-16, takes place through a stable and compact monomeric intermediate, with 31% the stability of the folded dimeric domain. Double jump multiple wavelength experiments allowed the reconstruction of the fluorescence spectrum of the monomeric intermediate at 100 milliseconds, indicating that tryptophan residues, otherwise buried in the folded state, are accessible to the solvent. Burial of surface area as well as differential behavior to ionic strength and pH with respect to the native ground state, plus the impossibility of having over 2500 Å2 of surface area of the half-barrel exposed to the solvent, indicates that the formation of a non-native compact tertiary structure precedes the assembly of native quaternary structure. The monomeric intermediate can dimerize, albeit with a weaker affinity (∼1 μM), to yield a non-native dimeric intermediate, which rearranges to the native dimer through a parallel folding channel, with a unimolecular rate-limiting step. Folding pathways from either acid or urea unfolded states are identical, making the folding model robust. Unfolding takes place through a major phase accounting for apparently all the secondary structure change, with identical rate constant to that of the fluorescence unfolding experiment. In contrast to the folding direction, no unfolding intermediate was found.